DIGITALISATION OF TAX AUDITS: THE USE OF ARTIFICIAL INTELLIGENCE AND BLOCKCHAIN IN FISCAL CONTROL - Дем’янишина, Олеся (SWorldJournal, 2026)
The article provides a comprehensive overview of the digitalisation of tax audits under the conditions of rapid technological transformation of public finance systems. It identifies key problems of traditional fiscal control, including limited audit effic